Increase in Enterovirus D68 Infections in Young Children, United Kingdom, 2006-2016 - Kamau, E; Harvala, H; Blomqvist, S; Nguyen, D; Horby, P; Pebody, R; Simmonds, P (Centers for Disease Control and Prevention, 2019)
We determined the change in seroprevalence of enterovirus D68 (EV-D68) in the United Kingdom in age-stratified cohorts from 2006 to 2016, the period during which EV-D68 emerged as a cause of severe respiratory disease occasionally leading to paralysis. Infections were acquired primarily in infants and young children, and incidence was markedly higher in 2016.